OVER YOUR DEAD MOTHER: RUMORS AND SECRETS IN STIFTER’S “TOURMALINE” - Behrmann, Nicola (Imaginations: Journal of Cross-Cultural Image Studies, 2011)
Despite his con dence that he could create a simple and lucid masterpiece of descriptive narration, Adalbert Stifter’s “Tourmaline” turned out to be the most obscure and complex tale in his story-collection Many-Colored Stones (1852). This essay traces the cryptological drive undermining the coherence and closure the realist nar- rator attempts to provide. Stifter’s abundant description of seemingly super uous details, the numerous narrative gaps and various rumors confuse any suf cient account of what really happened. The breaks and leaks in sto- rytelling can be understood as indices leading to a sub- merged work of mourning. The pedagogical intention organizing Stifter’s meticulous story-telling not only in this story turns upon itself through the incessant sup- ply of these commemorative indices or fragments. Not only is such pedagogy unable to nd an ef cient narra- tive mode, it also consistently undermines the authority whereby the instructor-narrator might come to terms with his own tale.